Syntax meets discourse: Locative and deictic (directional) inversion in English - Ojea, Ana (Poznan Studies in Contemporary Linguistics, 2020)
This paper offers a formal analysis of three constructions in English: , and . These constructions constitute thetic statements with a locative intentional base which sets a scene that (re)introduces an entity in the discourse; syntactically, they display a non-canonical word order and have a number of unusual grammatical properties which make them particularly interesting to show how syntax connects, and adapts, to discourse. I propose that they all obtain from a language particular mechanism which involves a functional category LocP that adjusts the computational requirement to have a preverbal subject to the intentional need to have the subject post-verbally. As for the differences among them, they are approached in terms of the features that head LocP and the lexical properties of the verbs that head each of the structures. Ultimately, the paper also serves to discuss the role of certain informational features (the so-called ) in the syntactic derivation.